A high-strength PET composite material and preparation method thereof
By using a mixed aerogel prepared by using a vapor-phase silica and graphene in PET materials, and composite swelling-type layered sodium silicate after grafting dopamine on its surface, PET composite materials with excellent high-strength and anti-aging properties were prepared, solving the problem of insufficient strength and anti-aging properties of existing PET materials.
Patent Information
- Application Number
- CN202411778115.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing PET materials have shortcomings in strength and anti-aging properties, especially glass fiber reinforced products have floating fiber problems, which affect performance and health and safety.
Hybrid filler-modified PET material was prepared by co-preparing mixed aerogels using vapor-phase silica and graphene, and composited with swelling-type layered sodium silicate after grafting dopamine on its surface.
The high strength and anti-aging performance of PET materials have been improved, and the stability and anti-aging ability of the material are improved through the nanoporous carbon network structure and self-patching mechanism.
Smart Images

Figure BDA0005172036650000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to a high-strength PET composite material and a preparation method thereof. Background Art
[0002] Polyethylene terephthalate (PET), as one of the five general-purpose engineering plastics, has outstanding toughness, aging resistance, creep resistance, friction and wear resistance. It is the largest and most widely used variety of thermoplastic linear saturated resin among polyesters. PET is light in weight, high in strength, good in air tightness, high in transparency, excellent in fatigue resistance, friction resistance and aging resistance, outstanding in electrical insulation, and has both certain rigidity and certain flexibility.
[0003] At present, the reinforcement of PET is mainly modified by adding glass fiber, but it is difficult for glass fiber to combine well with PET matrix, which will cause floating fiber phenomenon. The exposure of glass fiber will not only affect the performance of the material, but also affect the health of users. Therefore, Europe has restricted the import of glass fiber reinforced products. Finding substitutes or alternatives for PET material reinforced glass fiber to strengthen and toughen PET has an important impact on the expansion of the application field of PET composite materials. The present invention starts with hybrid modification of inorganic fillers to improve the shortcomings of the current PET material strength and make high-strength PET composite materials. Summary of the invention
[0004] The object of the present invention is to provide a high-strength PET composite material and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a high-strength PET composite material, wherein the composite material is prepared by preparing a mixed aerogel with fumed silica and graphene, grafting dopamine and then compounding swollen layered sodium silicate to prepare a hybrid filler modified PET as the core material.
[0006] Furthermore, a method for preparing a high-strength PET composite material comprises the following preparation steps:
[0007] (1) adding dried graphite oxide to deionized water to form a dispersion, then adding fumed silica, stirring at 120 rpm for 20 min, then ultrasonicating at 60 kHz for 20 min to prepare a mixed dispersion, then flash freezing the mixed dispersion in liquid nitrogen, and then drying the frozen mixed dispersion in a vacuum for 24 h at a vacuum degree of -0.085 MPa to prepare a mixed graphene oxide aerogel; heat treating the mixed graphene oxide aerogel in an inert atmosphere of argon gas, slowly raising the temperature from room temperature to The mixed aerogel is prepared by heating the mixture to 300°C and maintaining the temperature for 10 hours. Dopamine is mixed with deionized water to prepare a dopamine aqueous solution with a concentration of 2-10 g / ml. The mixed aerogel is added to the dopamine aqueous solution at a solid-liquid ratio of 1:5 so that the dopamine aqueous solution is impregnated with the mixed aerogel, and the mixture is slowly stirred at 60 rpm for 1 hour. Then, the swollen layered silicate is added and the mixture is slowly stirred at 60 rpm for 1 hour. After the reaction is completed, the solid is filtered and placed in a drying oven at 30°C for 3 hours to obtain a hybrid filler.
[0008] (2) 200 parts of PET polyester particles are melted at 265° C., 2-16 parts of hybrid filler, 1-4 parts of talc nucleating agent, 1-3 parts of 1,3-phenylene-bis(2-oxazoline) chain extender, and 2-7.5 parts of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid] pentaerythritol ester antioxidant are added, the mixture is stirred at 240 rpm for 10 minutes, and then extruded through a twin-screw + single-screw splicing extruder to form PET as a core material, which is then foamed using a hydrocarbon foaming agent; the PET polyester chip particles are foamed from particles to sheet-like PET core board materials by physical foaming (the product density can be customized according to customer requirements);
[0009] (3) Cut the PET core board into the required thickness and cut off the four sides to align the boards for bonding. Place the upper and lower surface decorative layers prepared in advance on the automatic glue spraying machine in turn, and spray the surface with a specified two-component polyurethane glue of 300g / ㎡. The two-component glue is divided into glue and curing agent. The mixing ratio is set on the equipment according to the ratio in the manual; first place the lower surface decorative layer (already sprayed with glue) on the platform, then place the PET core board, and then place the upper reinforcement layer (already sprayed with glue) on the upper surface to make it a whole, and finally add the upper surface decorative layer. After placement, the product needs to be aligned in the upper, middle and lower parts to avoid misalignment of the product after pressing and curing; then place the integrated PET composite board on the press, apply a pressure of 1MPa, and set the equipment to maintain the pressure for a specified time of 8h, and then automatically release the pressure after the parameters on the equipment reach the specified time to take out the final product.
[0010] Furthermore, the concentration of the graphene oxide dispersion in step (1) is 2.5 mg / mL.
[0011] Furthermore, in step (1), the molar ratio of graphene oxide to fumed silica is 1:0.3-1.
[0012] Furthermore, the heating rate of the slow heating in step (1) is 10°C / min.
[0013] Furthermore, in step (2), the temperature of the twin screw is about 280°C-300°C, and the temperature of the single screw is about 230°C-260°C.
[0014] Furthermore, in step (3), the reinforcing layer is a surface layer that does not contain harmful substances, such as metal sheets (such as aluminum, galvanized sheets, etc.), PET sheets, fireproof boards, acrylic, SPC, multilayer boards, ABS, melamine paper and natural solid wood.
[0015] Furthermore, the semi-finished product after the reinforcement layer is affixed in step (3) is passed through a PUR device and a corresponding surface decorative layer is affixed. The cost board after the decorative layer is affixed is placed in a designated constant temperature 23±1°C and constant humidity 50±2% room for static curing for 48 hours.
[0016] Furthermore, the surface decoration layer is one of PP / PVC / PETG films.
[0017] Furthermore, in the step (3), after the pressure relief is completed, the mixture is placed in a designated constant temperature room at 23±1°C and constant humidity room at 50±2% for 24 hours to ensure the quality of the final product.
[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0019] The present invention prepares a mixed aerogel with fumed silica and graphene, grafts dopamine to form a composite swollen layered sodium silicate, and prepares a hybrid filler-modified PET to form a composite material to achieve high strength and anti-aging effects.
[0020] First, fumed silica is used as an inorganic material to improve PET. Compared with ordinary silica, fumed silica has stronger surface activity, is rich in silanol and siloxy groups, and has a porous structure with a three-dimensional network. On this basis, fumed silica is added during the preparation of graphene aerogel. The siloxy groups on the surface of fumed silica combine with the hydroxyl groups of graphene oxide hydrogel. After heat treatment, a hybrid aerogel with a nanoporous carbon network structure and a network skeleton filled with a large amount of gaseous dispersion medium is formed. This can further improve the strength of the composite material and achieve an excellent hydrophobic effect.
[0021] Secondly, dopamine is grafted on the surface of the aerogel, and the amino group of dopamine undergoes dehydration condensation with the silanol group of silica to form a composite swelling layered silicate to prepare a hybrid filler; the hybrid filler improves its own dispersibility and compatibility in PET due to the dopamine grafted on its surface, thereby optimizing the stability of the composite material; during the use of the composite material, when fine cracks appear due to aging, on the one hand, the swelling layered silicate can swell by absorbing slightly acidic rainwater to fill the gaps and reduce the continued erosion of the material by rainwater; on the other hand, dopamine spontaneously reacts and polymerizes into polydopamine after contacting acidic rainwater, which can connect the cracks to form a self-repairing effect. At the same time, polydopamine has the function of scavenging free radicals, which can improve the aging process of the cracks, thereby making the strength of the composite material stable and improving the anti-aging performance. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0023] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of a high-strength PET composite material prepared in the following examples.
[0024] In order not to affect the experimental results, the reinforcing layers of the embodiment and the comparative example are all made of PET sheets. The overall length, width and height of the sample are 50cm*20cm*50cm, and the density of the PET core sheet is 115kg / m 3 .
[0025] Tensile strength: tested according to ASTM D638;
[0026] Flexural strength: tested according to ASTM D790;
[0027] Notched impact strength: tested according to ASTM D256.
[0028] Example 1
[0029] (1) adding dried graphite oxide to deionized water to form a dispersion with a concentration of 2.5 mg / mL, then adding fumed silica, the molar ratio of graphene oxide to fumed silica being 1:0.3, first stirring at 120 rpm for 20 min, then ultrasonicating at 60 kHz for 20 min to prepare a mixed dispersion, then flash freezing the mixed dispersion in liquid nitrogen, and then drying the frozen mixed dispersion in a vacuum for 24 h at a vacuum degree of -0.085 MPa to prepare a mixed graphene oxide aerogel; heat treating the mixed graphene oxide aerogel in an inert atmosphere of argon gas. The temperature was slowly raised from room temperature to 300°C and maintained at this temperature for 10 hours at a heating rate of 10°C / min, and a hybrid aerogel was obtained after heat treatment; dopamine was mixed with deionized water to obtain a dopamine aqueous solution with a concentration of 2g / ml; the hybrid aerogel was added to the dopamine aqueous solution at a solid-liquid ratio of 1:5 so that the dopamine aqueous solution was impregnated with the hybrid aerogel, and the mixture was slowly stirred at a speed of 60rpm for 1h, and then the swollen layered silicate was added, and the mixture was still slowly stirred at a speed of 60rpm for 1h; after the reaction was completed, the solid was filtered and placed in a drying oven at 30°C for 3h to obtain a hybrid filler;
[0030] (2) 200 parts of PET polyester particles are melted at 265° C., 2 parts of hybrid fillers, 1 part of talc nucleating agent, 1 part of 1,3-phenylene-bis(2-oxazoline) chain extender, and 2 parts of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid] pentaerythritol ester antioxidant are added, the mixture is stirred at 240 rpm for 10 min, and then extruded through a twin-screw + single-screw splicing extruder, the twin-screw temperature is about 280° C., and the single-screw temperature is about 230° C., to make PET as a core material, and then foamed using a hydrocarbon foaming agent; the polyester chip particles of PET are foamed from particles to sheets of PET core board material by physical foaming;
[0031] (3) Cut the PET core board into the required thickness and cut off the four sides to align the boards for bonding. Place the upper and lower surface decorative layers prepared in advance on the automatic glue spraying machine in turn. The decorative layer is a PP film, and a two-component polyurethane glue with a specified weight of 300g / ㎡ is sprayed on the surface. The two-component glue is divided into glue and curing agent. The mixing ratio is set on the equipment according to the ratio in the manual; first place the lower surface decorative layer (already sprayed with glue) on the platform, then place the PET core board, and then place the upper reinforcement layer (already sprayed with glue) on the upper surface to make it a whole. The semi-finished product after the reinforcement layer is pasted The product is then passed through the PUR equipment and the corresponding surface decoration layer is affixed. The products need to be aligned on the top, middle and bottom sides after placement to avoid misalignment of the products after pressing and curing. The cost board after the decorative layer is affixed is placed in a specified constant temperature of 22°C and a constant humidity of 48% for static curing for 48 hours; then the integrated PET composite board is placed on the press, a pressure of 1MPa is applied, and the equipment is set to maintain the pressure for a specified time of 8 hours. After the parameters on the equipment reach the specified time, the pressure is automatically released to take out the final product. After the pressure release is completed, it is placed in a specified constant temperature of 22°C and a constant humidity of 48% for static curing for 24 hours to ensure the quality of the final product.
[0032] Example 2
[0033] (1) adding dried graphite oxide to deionized water to form a dispersion with a concentration of 2.5 mg / mL, then adding fumed silica, the molar ratio of graphene oxide to fumed silica being 1:0.65, first stirring at 120 rpm for 20 min, then ultrasonicating at 60 kHz for 20 min to prepare a mixed dispersion, then flash freezing the mixed dispersion in liquid nitrogen, and then drying the frozen mixed dispersion in a vacuum for 24 h at a vacuum degree of -0.085 MPa to prepare a mixed graphene oxide aerogel; and thermally drying the mixed graphene oxide aerogel in an inert atmosphere of argon gas. treatment, slowly raising the temperature from room temperature to 300°C and maintaining the temperature for 10 hours, with a heating rate of 10°C / min, to obtain a hybrid aerogel after heat treatment; mixing dopamine with deionized water to obtain a dopamine aqueous solution with a concentration of 6 g / ml; adding the hybrid aerogel to the dopamine aqueous solution with a solid-liquid ratio of 1:5 to impregnate the hybrid aerogel with the dopamine aqueous solution, slowly stirring at a speed of 60 rpm for 1 hour, then adding the swollen layered silicate, and still slowly stirring at a speed of 60 rpm for 1 hour; after the reaction is completed, filtering and obtaining the solid, and placing it in a 30°C drying oven for 3 hours to obtain a hybrid filler;
[0034] (2) 200 parts of PET polyester particles are melted at 265° C., 9 parts of hybrid filler, 2.5 parts of talc nucleating agent, 2 parts of 1,3-phenylene-bis(2-oxazoline) chain extender, and 4.75 parts of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid] pentaerythritol ester antioxidant are added, the mixture is stirred at 240 rpm for 10 min, and then extruded through a twin-screw + single-screw splicing extruder, the twin-screw temperature is about 290° C., and the single-screw temperature is about 245° C., to make PET as a core material, and then foamed with a hydrocarbon foaming agent; the polyester chip particles of PET are foamed from particles to sheets of PET core board material by physical foaming;
[0035] (3) Cut the PET core board into the required thickness and cut off the four sides to align the boards for bonding. Place the upper and lower surface decorative layers prepared in advance on the automatic glue spraying machine in turn. The decorative layer is a PVC film, and a two-component polyurethane glue with a specified weight of 300g / ㎡ is sprayed on the surface. The two-component glue is divided into glue and curing agent. The mixing ratio is set on the equipment according to the ratio in the manual; first place the lower surface decorative layer (already sprayed with glue) on the platform, then place the PET core board, and then place the upper reinforcement layer (already sprayed with glue) on the upper surface to make it a whole. The half after the reinforcement layer is pasted The finished product then passes through the PUR equipment and is affixed with the corresponding surface decorative layer. The product needs to be aligned on the top, middle and bottom after placement to avoid misalignment of the product after pressing and curing. The cost board after the decorative layer is affixed is placed in a specified constant temperature of 23°C and a constant humidity of 50% for static curing for 48 hours; then the integrated PET composite board is placed on the press, a pressure of 1MPa is applied, and the equipment is set to maintain the pressure for a specified time of 8 hours. After the parameters on the equipment reach the specified time, the pressure is automatically released to take out the final product. After the pressure release is completed, it is placed in a specified constant temperature of 23°C and a constant humidity of 50% for static curing for 24 hours to ensure the quality of the final product.
[0036] Example 3
[0037] (1) adding dried graphite oxide to deionized water to form a dispersion with a concentration of 2.5 mg / mL, then adding fumed silica, the molar ratio of graphene oxide to fumed silica being 1:1, first stirring at 120 rpm for 20 min, then ultrasonicating at 60 kHz for 20 min to prepare a mixed dispersion, then flash freezing the mixed dispersion in liquid nitrogen, and then drying the frozen mixed dispersion in a vacuum for 24 h at a vacuum degree of -0.085 MPa to prepare a mixed graphene oxide aerogel; heat treating the mixed graphene oxide aerogel in an inert atmosphere of argon gas , slowly raising the temperature from room temperature to 300°C and maintaining the temperature for 10 hours at a heating rate of 10°C / min, and obtaining a hybrid aerogel after heat treatment; mixing dopamine with deionized water to obtain a dopamine aqueous solution with a concentration of 10 g / ml; adding the hybrid aerogel to the dopamine aqueous solution at a solid-liquid ratio of 1:5 to impregnate the hybrid aerogel with the dopamine aqueous solution, slowly stirring at 60 rpm for 1 hour, then adding the swollen layered silicate, and still slowly stirring at 60 rpm for 1 hour; after the reaction is completed, filtering and obtaining the solid, and placing it in a 30°C drying oven for 3 hours to obtain a hybrid filler;
[0038] (2) 200 parts of PET polyester particles are melted at 265° C., 16 parts of hybrid filler, 4 parts of talc nucleating agent, 3 parts of 1,3-phenylene-bis(2-oxazoline) chain extender, and 7.5 parts of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid] pentaerythritol ester antioxidant are added, the mixture is stirred at 240 rpm for 10 min, and then extruded through a twin-screw + single-screw splicing extruder, the twin-screw temperature is about 300° C., and the single-screw temperature is about 260° C., to make PET as a core material, and then foamed with a hydrocarbon foaming agent; the polyester chip particles of PET are foamed from particles to sheets of PET core board material by physical foaming;
[0039] (3) Cut the PET core board into the required thickness and cut off the four sides to align the boards for bonding. Place the upper and lower surface decorative layers prepared in advance on the automatic glue spraying machine in turn. The decorative layer is PETG film, and sprinkle the surface with a specified 300g / ㎡ two-component polyurethane glue. The two-component glue is divided into glue and curing agent. The mixing ratio is set on the equipment according to the ratio in the manual; first place the lower surface decorative layer (already sprinkled with glue) on the platform, then place the PET core board, and then place the upper reinforcement layer (already sprinkled with glue) on the upper surface to make it a whole. The half after the reinforcement layer is pasted The finished product then passes through the PUR equipment and is affixed with the corresponding surface decorative layer. The product needs to be aligned on the top, middle and bottom after placement to avoid misalignment of the product after pressing and curing. The cost board after the decorative layer is affixed is placed in a specified constant temperature of 24°C and a constant humidity of 52% for static curing for 48 hours; then the integrated PET composite board is placed on the press, a pressure of 1MPa is applied, and the equipment is set to maintain the pressure for a specified time of 8 hours. After the parameters on the equipment reach the specified time, the pressure is automatically released to take out the final product. After the pressure release is completed, it is placed in a specified constant temperature of 24°C and a constant humidity of 52% for static curing for 24 hours to ensure the quality of the final product.
[0040] Comparative Example 1
[0041] The difference between Comparative Example 1 and Example 2 is that step (1) is different. Step (1) is changed to: adding dried graphite oxide to deionized water, stirring at 120 rpm for 20 min, and then ultrasonicating at 60 kHz for 20 min to prepare a dispersion, then flash freezing the dispersion in liquid nitrogen, and then drying the frozen dispersion in a vacuum for 24 h at a vacuum degree of -0.085 MPa to prepare graphene oxide aerogel; heat treating the graphene oxide aerogel in an inert atmosphere of argon gas, slowly raising the temperature from room temperature to 300 ° C. The temperature was maintained for 10 hours with a heating rate of 10°C / min, and aerogel was obtained after heat treatment; dopamine was mixed with deionized water to obtain a dopamine aqueous solution with a concentration of 6 g / ml; aerogel was added to the dopamine aqueous solution with a solid-liquid ratio of 1:5 to impregnate the aerogel with the dopamine aqueous solution, and the mixture was slowly stirred at 60 rpm for 1 hour, and then the swollen layered silicate was added, and the mixture was still slowly stirred at 60 rpm for 1 hour; after the reaction was completed, the solid was filtered and placed in a 30°C drying oven for 3 hours to obtain a hybrid filler; the remaining steps were the same as in Example 2.
[0042] Comparative Example 2
[0043] The difference between Comparative Example 2 and Example 2 lies in the difference in step (1), where step (1) is modified as follows: adding dried graphite oxide to deionized water to form a dispersion with a concentration of 2.5 mg / mL, then adding fumed silica, the molar ratio of graphene oxide to fumed silica being 1:0.65, stirring at 120 rpm for 20 min, and then ultrasonicating at 60 kHz for 20 min to prepare a mixed dispersion; mixing dopamine with deionized water to prepare a dopamine aqueous solution with a concentration of 6 g / ml; adding the mixed dispersion to the dopamine aqueous solution, the mass ratio of the two solutions being 1:1, slowly stirring at 60 rpm for 1 h, then adding swollen layered silicate, and still slowly stirring at 60 rpm for 1 h; after the reaction is completed, filtering and taking out the solid, placing it in a drying oven at 30° C. for 3 h to prepare a hybrid filler; and the remaining steps are the same as those in Example 2.
[0044] Comparative Example 3
[0045] The difference between Comparative Example 3 and Example 2 is that step (1) is different. Step (1) is changed to: dry graphite oxide is added to deionized water to form a dispersion with a concentration of 2.5 mg / mL, and then fumed silica is added, the molar ratio of graphene oxide to fumed silica is 1:0.65, first stirring at 120 rpm for 20 min, and then ultrasonicating at 60 kHz for 20 min to prepare a mixed dispersion, and then the mixed dispersion is flash frozen in liquid nitrogen, and then the frozen mixed dispersion is dried in vacuum for 24 h, and the vacuum degree is -0.08 5MPa to prepare a mixed graphene oxide aerogel; heat-treating the mixed graphene oxide aerogel in an inert atmosphere of argon, slowly raising the temperature from room temperature to 300°C and maintaining the temperature for 10 hours, with a heating rate of 10°C / min, to obtain a mixed aerogel after heat treatment; adding the mixed aerogel into deionized water with a solid-to-liquid ratio of 1:5, adding a swollen layered silicate, and slowly stirring at a speed of 60rpm for 1 hour; after the reaction is completed, filtering and taking out the solid, and placing it in a drying oven at 30°C for 3 hours to obtain a hybrid filler; and the remaining steps are the same as those in Example 2.
[0046] Comparative Example 4
[0047] The difference between Comparative Example 4 and Example 2 is that step (1) is different. Step (1) is changed to: dry graphite oxide is added to deionized water to form a dispersion with a concentration of 2.5 mg / mL, and then fumed silica is added, the molar ratio of graphene oxide to fumed silica is 1:0.65, first stirring at 120 rpm for 20 min, then ultrasonicating at 60 kHz for 20 min to prepare a mixed dispersion, and then flash freezing the mixed dispersion in liquid nitrogen, and then drying the frozen mixed dispersion in vacuum for 24 h, the vacuum degree is -0.085 MPa, to prepare a mixed graphene oxide aerogel ; The mixed graphene oxide aerogel is heat treated in an inert atmosphere of argon, the temperature is slowly increased from room temperature to 300°C and maintained at this temperature for 10 hours, the heating rate is 10°C / min, and a mixed aerogel is obtained after the heat treatment; dopamine is mixed with deionized water to prepare a dopamine aqueous solution with a concentration of 6 g / ml; the mixed aerogel is added to the dopamine aqueous solution with a solid-liquid ratio of 1:5 so that the dopamine aqueous solution is impregnated with the mixed aerogel, and the mixture is slowly stirred at 60 rpm for 1 hour; after the reaction is completed, the solid is filtered and placed in a 30°C drying oven for 3 hours to obtain a hybrid filler; the remaining steps are the same as in Example 2.
[0048] Effect example
[0049] Table 1 below shows the performance analysis results of a high-strength PET composite material using Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.
[0050] Table 1
[0051]
[0052] From the comparison of the experimental data of tensile strength, bending strength and impact strength of the embodiment and the comparative example, it can be found that the present invention uses fumed silica as an inorganic material for improving PET. Compared with ordinary silica, fumed silica has stronger surface activity, is rich in silanol and siloxy groups, and has a porous structure with a three-dimensional network. On this basis, fumed silica is added during the preparation of graphene aerogel, and the siloxy groups on the surface of fumed silica are combined with the hydroxyl groups of graphene oxide hydrogel. After heat treatment, a hybrid aerogel with a nanoporous carbon network structure and a network skeleton filled with a large amount of gaseous dispersion medium is formed, which can further improve the strength of the composite material and achieve excellent hydrophobic effect. From the comparison of the experimental data of the tensile strength retention rate after 60 days outdoors of the embodiment and the comparative example, it can be found that in the present invention, dopamine is grafted on the surface of the aerogel, and the amino group of dopamine and the silanol group of silica undergo dehydration condensation to form a composite swelling layered silicate to prepare a hybrid filler; the hybrid filler improves its own dispersibility and compatibility in PET due to the dopamine grafted on its surface, and optimizes the stability of the composite material; during the use of the composite material, when fine cracks appear due to aging, on the one hand, the swelling layered silicate can swell by absorbing slightly acidic rainwater to fill the gaps, thereby reducing the continued erosion of the material by rainwater; on the other hand, after contacting acidic rainwater, dopamine spontaneously reacts and polymerizes to form polydopamine, which can connect the cracks to form a self-repairing effect. At the same time, polydopamine has the function of scavenging free radicals, which can improve the aging process of the cracks, so that the strength of the composite material is stable and the anti-aging performance is improved.
[0053] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A high-strength PET composite material, characterized in that: The composite material is prepared by preparing a mixed aerogel with fumed silica and graphene, grafting dopamine onto composite swollen layered sodium silicate, and preparing hybrid filler modified PET as the core material.
2. A method for preparing a high-strength PET composite material, characterized in that: The method comprises the following preparation steps: (1) adding dried graphite oxide to deionized water to form a dispersion, then adding fumed silica, stirring at 120 rpm for 20 min, then ultrasonicating at 60 kHz for 20 min to prepare a mixed dispersion, then flash freezing the mixed dispersion in liquid nitrogen, and then drying the frozen mixed dispersion in a vacuum for 24 h at a vacuum degree of -0.085 MPa to prepare a mixed graphene oxide aerogel; heat treating the mixed graphene oxide aerogel in an inert atmosphere of argon gas, slowly raising the temperature from room temperature to The mixed aerogel is prepared by heating the mixture to 300°C and maintaining the temperature for 10 hours. Dopamine is mixed with deionized water to prepare a dopamine aqueous solution with a concentration of 2-10 g / ml. The mixed aerogel is added to the dopamine aqueous solution at a solid-liquid ratio of 1:5 so that the dopamine aqueous solution is impregnated with the mixed aerogel, and the mixture is slowly stirred at 60 rpm for 1 hour. Then, the swollen layered silicate is added and the mixture is slowly stirred at 60 rpm for 1 hour. After the reaction is completed, the solid is filtered and placed in a drying oven at 30°C for 3 hours to obtain a hybrid filler. (2) 200 parts of PET polyester particles are melted at 265° C., 2-16 parts of hybrid filler, 1-4 parts of talc nucleating agent, 1-3 parts of 1,3-phenylene-bis(2-oxazoline) chain extender, and 2-7.5 parts of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid] pentaerythritol ester antioxidant are added, the mixture is stirred at 240 rpm for 10 minutes, and then extruded through a twin-screw + single-screw spliced extruder to form PET as a core material, and then foamed with a hydrocarbon foaming agent; the PET polyester chip particles are foamed from particles to sheet-like PET core board materials through physical foaming; (3) Cut the PET core board into the required thickness and cut off the four sides to align the boards for bonding. Place the upper and lower surface decorative layers prepared in advance on the automatic glue spraying machine in turn, and spray the surface with a specified two-component polyurethane glue of 300g / ㎡. The two-component glue is divided into glue and curing agent. The mixing ratio is set on the equipment according to the ratio in the manual; first place the lower surface decorative layer (already sprayed with glue) on the platform, then place the PET core board, and then place the upper reinforcement layer (already sprayed with glue) on the upper surface to make it a whole, and finally add the upper surface decorative layer. After placement, the product needs to be aligned in the upper, middle and lower parts to avoid misalignment of the product after pressing and curing; then place the integrated PET composite board on the press, apply a pressure of 1MPa, and set the equipment to maintain the pressure for a specified time of 8h, and then automatically release the pressure after the parameters on the equipment reach the specified time to take out the final product.
3. The method for preparing a high-strength PET composite material according to claim 2, characterized in that: The concentration of the graphene oxide dispersion in the step (1) is 2.5 mg / mL.
4. The method for preparing a high-strength PET composite material according to claim 2, characterized in that: In the step (1), the molar ratio of graphene oxide to fumed silicon dioxide is 1:0.3-1.
5. The method for preparing a high-strength PET composite material according to claim 2, characterized in that: The heating rate of the slow heating in step (1) is 10°C / min.
6. The method for preparing a high-strength PET composite material according to claim 2, characterized in that: In step (2), the temperature of the twin screw is about 280°C-300°C, and the temperature of the single screw is about 230°C-260°C.
7. The method for preparing a high-strength PET composite material according to claim 2, characterized in that: In the step (3), the reinforcing layer is a surface layer that does not contain harmful substances, such as metal sheets (such as aluminum, galvanized sheets, etc.), PET sheets, fireproof boards, acrylic, SPC, multilayer boards, ABS, melamine paper and natural solid wood.
8. The method for preparing a high-strength PET composite material according to claim 2, characterized in that: The semi-finished product after the reinforcement layer is affixed in the step (3) is then passed through the PUR equipment and affixed with the corresponding surface decoration layer. The cost board after affixing the decoration layer is placed in a designated constant temperature 23±1°C and constant humidity 50±2% room for static curing for 48 hours.
9. The method for preparing a high-strength PET composite material according to claim 8, characterized in that: The surface decoration layer is one of PP / PVC / PETG films.
10. The method for preparing a high-strength PET composite material according to claim 2, characterized in that: In the step (3), after the pressure relief is completed, the mixture is placed in a designated constant temperature room at 23±1°C and constant humidity room at 50±2% for 24 hours to ensure the quality of the final product.
Citation Information
Cited By
Warm-keeping and health-care composite fabric and preparation method thereof
CN119777051A
A warm and healthy composite fabric and a preparation method thereof
CN119777051B
High-strength PET composite material and preparation method thereof
CN120665404A